Role Of Zeolities In Catalytic Abatement Of Volatile Organic Compunds VOCs Pollution. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2002)
This article reviews the role of zeolites in the abatement of VOC emission to the atmosphere. The incorporation of metal species into zeolites' lattice structure through ion exchange will convert these materiats into effective catalysts for VOC removal.